2000
DOI: 10.1046/j.1524-4725.2000.99197.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopeeling (Extensive Cryosurgery) for Treatment of Actinic Keratoses: An Update and Comparison

Abstract: Extensive cryosurgery (cryopeeling) is a highly effective method for removing actinic keratoses and preventing recurrences. The subsequent incidence of squamous cell carcinoma is also greatly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
1
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 21 publications
0
44
1
6
Order By: Relevance
“…The phototoxic reactions with erythema and edema seen in this study were considerable in intensity and associated with discomfort during the first 48 hours after treatment, but these reactions abated relatively rapidly in most patients, in sharp contrast to cryotherapy 41 or topical chemotherapy with fluorouracil 42 or imiquimod. [15][16][17] Despite the lack of uniformity in incubation times, light sources, drug vehicles, and exposure times and fluences, published studies on PDT demonstrate considerable efficacy for AKs.…”
mentioning
confidence: 54%
“…The phototoxic reactions with erythema and edema seen in this study were considerable in intensity and associated with discomfort during the first 48 hours after treatment, but these reactions abated relatively rapidly in most patients, in sharp contrast to cryotherapy 41 or topical chemotherapy with fluorouracil 42 or imiquimod. [15][16][17] Despite the lack of uniformity in incubation times, light sources, drug vehicles, and exposure times and fluences, published studies on PDT demonstrate considerable efficacy for AKs.…”
mentioning
confidence: 54%
“…Taking these facts into account, it becomes obvious that cryotherapy/cryosurgery response rates may, indeed, widely vary by freeze time, extent of treated field and practitioner technique, as previously reported 11,30,34,35 . On the other hand, lege artis cryosurgery presents high cure rates in the hands of experienced cryosurgeons [26][27][28][29][30][31][32]36 and is widely available. Indeed, studies concentrated to cryosurgery with N 2 O or liquid nitrogen revealed high cure rates of 74-100% 1.5-12 months after treatment [26][27][28][29][30][31][32] .…”
mentioning
confidence: 99%
“…On the other hand, lege artis cryosurgery presents high cure rates in the hands of experienced cryosurgeons [26][27][28][29][30][31][32]36 and is widely available. Indeed, studies concentrated to cryosurgery with N 2 O or liquid nitrogen revealed high cure rates of 74-100% 1.5-12 months after treatment [26][27][28][29][30][31][32] .…”
mentioning
confidence: 99%
“…O fotoenvelhecimento pode ser tratado e/ou prevenido por meio de métodos clinicos ou cirúrgicos como: uso de substâncias químicas como as esfoliações, métodos mecânicos como a dermoabrasão, ou cirúrgicos como a eletrocoagulação, crioterapia ou laserterapia (Quadro 5) 25,[83][84][85][86][87][88] .…”
Section: Tratamento Do Fotoenvelhecimentounclassified